PENGARUH PEMBERIAN AROMATERAPI LEMON TERHADAP NYERI PERSALINAN KALA I FASE AKTIF DI BPM NY INDAH MAYA, Amd.KebDESA TUNJUNGMEKAR KECAMATAN KALITENGAH KABUPATEN LAMONGAN - Turlina, Lilin; Hikmah, Fikriyah Nailul (Universitas Muhammadiyah Lamongan, 2021)
Background: Birth processes are identical to the pain that will be lived. So that both mother and health officer make a lot of effort to reduce the pain of labor. Aromatherapy can be given to help reduce anxiety, stress, fear, nausea, vomiting and pain.Objectives: The purpose of this study is to know Knowing the Influence of Lemon Aromatherapy on Intensity of Kala I Labor Pain I Active Phase In Midwife Ny. Indah Maya, Amd.Keb Tunjungmekar Village Kalitengah Subdistrict Lamongan Regency Year 2017.Design: The research design used was one group pretest-posttest design, using Simple Random Sampling technique. Obtained the number of samel as many as 29 mothers gave birth At BPM Ny. Indah Maya, Amd.Keb Tunjungmekar Village, Kalitengah Sub-district, Lamongan District. This research data is the result of VDS scale measurement (Verbal Descritive Scale) on the observation sheet with Paired t-testResult: The result showed that the average of maternal pain intensity before giving lemon aromatherapy tended to experience severe pain compared to after being given lemon aromather having moderate pain. From the result of Paired Sample T-Test test, the value of t = 8.573 and p = (0.000), where p <(0,05) H1 is accepted, meaning that there is influence of lemon aromatherapy in reducing pain in maternal mother.Conclusions: It is recommended from the results of this study that lemon aromatherapy can be used as an intervention to first-time maternity women in the active phase. Keywords: Lemon Aromatherapy, Labor Pain, Labor Kala I Active Phase